A new method for measuring osteoclast formation by electrical impedance - Haruka Emori; Shinichi Iwai; Kakei Ryu; Hitoshi Amano; Takehiko Sambe; Takahiro Kobayashi; Tatsunori Oguchi; Kiyoshi Ohura; Katsuji Oguchi (Elsevier, 2015)
Osteoclasts are important target cells for osteoporosis treatment. Recently, a real-time cell analysis (RTCA) system was developed to observe cell morphology and adhesion; however, the use of RTCA to study osteoclastogenesis has not been reported. Here, we investigated whether osteoclast formation could be monitored in real-time using RTCA. The cell index determined via electrical impedance using RTCA, and the number of osteoclasts exhibited a significant positive correlation. RTCA was useful for determining the effect of (−)-epigallocatechin-3-gallate on the inhibition of bone resorption. We established a new method of measuring osteoclast formation in real-time using RTCA.